Insuring Supplıer Credıt Rısk In Exports To Promote Export Growth And Economic Development - Çetiner, Emine Müge; Eke, Selda (My University, 2018)
Purpose- The purpose of this study is to evaluate the effectiveness of the insured trade credit on the international trade abroad and in our country and to raise awareness about the issue that has great potential for growth in our country in the future. Methodolgy- The studies investigating the effect of the insured open account trade by private and officially supported export credit agencies on the development of exports and in general international trade were examined. The effect of export growth on economic development has been examined in order to assess the impact of export credit insurance. The fundamental concepts with the literature review have been summarized. Findings- Through the literature review, the following facts have been obtained. Supplier credit leads to the increase in sales of the supplier and that in turn leads to company growth. It is also an important financing source for the buyer who buys on credit also sells on credit and that leads to an increase in trade flows. It is complementary and alternative to bank loans especially in the periods of financial constraints when the companies are in need of working capital finance. Insured open account trade has a quite significant effect on increasing the exports of the country. At macro level, there is a dual causality relationship between export growth and economic development. Conclusion- As the result of the study, it has been concluded that the insured trade credit promotes the growth of trade flows and supply chains that would lead to the growth in trade volumes and economic growth.

Amaç- Bu çalışmada amaçlanan gerek ülkemizde gerekse yurtdışında sigortalanmış kredili ticaretin dış ticaret üzerindeki etkisinin araştırılması ve konunun önemi üzerinde farkındalık yaratarak ülkemizde gelecekte çok büyüyebilecek bir potansiyele dikkat çekmektir. Yöntem- Resmi destekli ihracat kredi sigortası ya da özel sektör kredi sigortası kuruluşları tarafından sigortalanan açık hesap ticaretin, ihracatın ve genel olarak uluslararası ticaretin gelişimine olan desteği konusunda yapılan çalışma örnekleri incelenmiştir. İhracatın ekonomik büyüme üzerindeki etkisi üzerinde durularak, ihracat kredi sigortası desteği irdelenmiştir. Temel kavramlar ve literatür çalışmaları özetlenmiştir. Bulgular- Literatür taraması sonucunda elde edilen bulgular şunlardır: Tedarikçi kredisi, tedarikçi firmaların satışlarını arttırarak firma büyümesine katkı sağlamaktadır. Alıcı firmalar için de önemli bir finansman kaynağı olmaktadır. Alıcı şirketin kendisi de müşterilerine kredili satış yapabildiğinden, ticari akımlarda artış sağlanmaktadır. Tedarikçi kredisi, işletme sermayesi finansman ihtiyacının karşılanmasında, özellikle finansal sıkışıklıkların olduğu dönemlerde şirketler için banka kredisine alternatif ve tamamlayıcı bir finansman kaynağı olmaktadır. Açık hesap ticaretin sigortalanması, ülkenin ihracatını arttırma konusunda son derece önemli bir role sahiptir. Makro düzeyde, ihracatın büyümesi ile ekonomik gelişme arasında da iki yönlü bir nedensellik ilişkisi bulunmaktadır. Sonuç- Çalışmada sigortalanmış kredili satışların ticari akımlarda büyümeyi destekleyeceği, tedarik zincirlerinin büyümesine neden olmaları sonucunda da, ticaret hacminin artmasına, ekonomik büyümeye katkı sağlayacakları sonucuna ulaşılmıştır.
İhracat Artışının ve Ekonomik Büyümenin Sağlanmasına Yönelik Olarak İhracatta Tedarikçi Kredi Riskinin Sigortalanması
Keywords: Tedarikçi Kredisi; Kredili Ticaret; Açık Hesap Ticaret; İhracat Kredi Sigortası; Kredi Sigortası; Supplier Credit; Trade Credit; Open Account Trade; Export Credit İnsurance; Credit Insurance